14.7k views
4 votes
Solve for h.
-12h + 4 = 0

User Rob VS
by
4.8k points

2 Answers

6 votes

Answer:

h =1/3

Explanation:


-12h + 4 = 0\\\\\mathrm{Subtract\:}4\mathrm{\:from\:both\:sides}\\-12h+4-4=0-4\\\\\mathrm{Simplify}\\-12h=-4\\\\\mathrm{Divide\:both\:sides\:by\:}-12\\(-12h)/(-12)=(-4)/(-12)\\\\Simplify\\h=(1)/(3)

User Muhammad Shareyar
by
5.3k points
4 votes

Answer:


h=1/3

Explanation:

So we have the equation:


-12h+4=0

Subtract 4 from both sides:


(-12h+4)-4=(0)-4\\-12h=-4

Divide both sides by -12:


(-12h)/-12=(-4)/-12\\h=-4/-12

Simplify and reduce:


h=1/3

User Praveen Murali
by
4.7k points